A text-based visual notation for the unit testing of model-driven tools. (September 2017) - Strüber, Daniel; Rieger, Felix; Taentzer, Gabriele
Abstract: During the unit testing of model-driven tools, a large number of models and test classes needs to be managed and maintained. Typically, some of these artifacts are specified manually, some are generated automatically. Existing approaches to test management rely on the available visual and textual modeling notations. As these notations are not tailored to unit testing, distinct maintainability trade-offs arise. In this paper, we propose a notation that aims to combine the benefits of visual and text-based approaches. The notation is at the same time visual and text-based, as it uses ASCII characters to emulate the familiar graphical notations. In our evaluation based on real models, we identify problematic model shapes challenging the scalability our notation, while finding that it is well-suited to capture typical test models. Highlights: We propose a notation that balances trade-offs between textual and visual notations. Our evaluation includes models from real test suites and an online repository. The text-based visual notation is well-suited to capture typical test models. The approach has specific benefits for reuse- and collaboration-intensive settings.